A compensatory framework for sustainable development: the case of Tanzania - Mtoni, Paul E (Cranfield University, 2010)
Development projects, such as plantations and infrastructure improvements, provide benefits for people at the regional and national scales. They can also result in negative impacts and costs borne by some members of society. Projects are deemed worthwhile if overall welfare is enhanced and, in principle, the gainers could compensate the losers. In this respect, compensation is an important measure or method of redistribution of benefits and costs between the gainers and losers in the context of development projects. It is also a potential strategy for addressing concerns of social justice, fairness, equity and disputes through negotiation. This research explores the potential use of compensation for promoting the sustainability of development projects and rural livelihoods in the context of developing economy, namely Tanzania. The literature review and exploratory visits to the study area revealed relevant theories, concepts and practical issues of compensation. An innovative framework that integrates the Coase theorem, Millennium ecosystem approach and the concepts of sustainable livelihoods was developed and used in assessing and analysing compensation practices of two project case studies. The research adapted a case study strategy for studying compensation in its geographical settings. Tanzania was used as the country case from which the teak and gaspipeline projects were selected as project case studies. One village in each project area was selected for detailed study. Key informants and focus group interviews provided initial insights into project impacts and compensation regimes. Twelve in-depth case studies were carried out on affected households. Key sustainability issues pertinent to compensation, people’s livelihoods and projects were verified using a questionnaire survey that involved 120 households. Other two surveys were carried out to collect views on compensation views in Tanzania from project developers and service providers. Triangulation of research methods, tools and sources of information enhanced quality of both qualitative and quantitative information. Cont/d.